2017
DOI: 10.1016/j.physletb.2017.07.057
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic phase transition of a black hole in rainbow gravity

Abstract: In this letter, using the rainbow functions that were proposed by Magueijo and Smolin, we investigate the thermodynamics and the phase transition of rainbow Schwarzschild black hole. First, we calculate the rainbow gravity corrected Hawking temperature. From this modification, we then derive the local temperature, free energy, and other thermodynamic quantities in an isothermal cavity. Finally, we analyze the critical behavior, thermodynamic stability, and phase transition of the rainbow Schwarzschild black ho… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 99 publications
(44 citation statements)
references
References 79 publications
4
40
0
Order By: Relevance
“…The acceleration (82) contains the singularity due to 푖 ∼ 1/√ 2 − (k k); that is, at V = the acceleration becomes orthogonal to the velocity, but remains divergent. Besides, due to dependence of effective metric on spin, we arrive at rather unusual picture of the Universe with rainbow geometry (some models of doubly special relativity predict rainbow geometry at Planck scale [54][55][56][57]): there is no unique spacetime manifold for the Universe of spinning particles: each particle will probe its own three-dimensional geometry. We conclude that MPTD equations do not seem promising candidate for the description of a relativistic rotating body.…”
Section: Advances In Mathematical Physicsmentioning
confidence: 97%
“…The acceleration (82) contains the singularity due to 푖 ∼ 1/√ 2 − (k k); that is, at V = the acceleration becomes orthogonal to the velocity, but remains divergent. Besides, due to dependence of effective metric on spin, we arrive at rather unusual picture of the Universe with rainbow geometry (some models of doubly special relativity predict rainbow geometry at Planck scale [54][55][56][57]): there is no unique spacetime manifold for the Universe of spinning particles: each particle will probe its own three-dimensional geometry. We conclude that MPTD equations do not seem promising candidate for the description of a relativistic rotating body.…”
Section: Advances In Mathematical Physicsmentioning
confidence: 97%
“…Note that the prediction of a minimal measurable length in order of Planck length in various theories of quantum gravity restricts the maximum energy that any particle can attain to the Planck energy. This implied the modification of linear momentum and also quantum commutation relations and results the modified dispersion relation, e.g., gravity's rainbow [50], see some particular cosmological [51][52][53] and astrophysical implications [54][55][56][57][58]. Moreover, this scale naturally arises in theories of quantum gravity in the form of an effective minimal uncertainly in positions ∆x 0 > 0.…”
Section: The Casimir Effect Under the Generalized Uncertainty Primentioning
confidence: 99%
“…Recently, according to the rainbow functions that were proposed by Magueijo and Smolin, we discussed the thermodynamics and phase transition of a spherically symmetric black hole. Our calculations showed that the RG changes the picture of black hole's thermodynamic phase transition [36]. In addition, we found three Hawking-Page-type phase transitions in the framework of the RG.…”
Section: Introductionmentioning
confidence: 55%